Measurement of Fibrinopeptide A in Patients Treated with Phenoprocoumon - Harenberg, J; Haas, R; Zimmermann, R (Thrombosis and Haemostasis, 1981)
Fibrinopeptide A (FPA), which is considered to be a quantitative indicator for the thrombin activity in vivo, was measured in 136 patients treated with phenprocoumon in order to obtain information on the effectiveness of the inhibition of the coagulation system. The results show a decrease of the FPA concentration in relation to the efficacy of the anticoagulant therapy as measured by the thrombotest coagulation method (p<0.01). However, elevated FPA was observed even under an effective oral anticoagulation.These data indicate that an increased thrombin activity cannot be completely prevented by oral anticoagulants in every patient. Combined measurement of FPA and the thrombotest coagulation method might be used to detect patients with an elevated risk of recurrent thromboembolism despite treatment with phenprocoumon.
Keywords: Fibrinopeptide A; Antithrombotic therapy; Oral anticoagulants; Phenprocoumon; Hypercoagulability of plasma